Perceptions of Verbal Toxic Positivity in Academic Interactions: A Study among University Students - Harida, Ratri; Mustikasari, Rizki; Novitasari, Lusy (Altruistik : Jurnal Konseling dan Psikologi Pendidikan, 2025)
This research aims to explore students' perceptions of the phenomenon of verbal toxic positivity in academic interactions, particularly between lecturers and students. Toxic positivity is a form of communication that conveys positive messages excessively without considering the emotional context of the recipient, which can actually have a negative impact on mental health. Using a descriptive quantitative method, data were collected through questionnaires distributed to 81 students of the English Education Study Program at STKIP PGRI Ponorogo. The research results show that the most dominant form of verbal toxic positivity is in the form of advice and affirmation. The main triggering situation is the continuous repetition of those statements by the lecturer, especially when students are experiencing emotional stress. The psychological impacts most felt by students are low self-esteem, feelings of depression, and the inability to express emotions in a healthy way. These findings emphasize the importance of faculty awareness, both as educators and academic advisors, in building empathetic and adaptive communication to create an academic environment that supports students' mental well-being. This study also recommends the development of communication and student well-being training to avoid the practice of verbal toxic positivity in the context of academics and academic guidance.